Obtaining soybean peroxidase from soybean hulls and its application for detoxification of 2,4-dichlorophenol contaminated water - Fernandes M. (2020)
© 2020 Elsevier Ltd. All rights reserved.This work aimed to evaluate the performance of soybean peroxidase on 2,4-dichlorophenol bioconversion. Soybean peroxidase was obtained from transgenic cultivar and purified to homogeneity followed by enzymatic characterisation using pyrogallol as standard substrate and applied to 2,4-dichlorophenol bioconversion. The results demonstrated that soybean peroxidase optimal conditions of pH and temperature were 6.5 and 71.6°C using pyrogallol as substrate. Regarding the 2,4-dichlorophenol bioconversion, removal of 80 % and 96 % was achieved in 1 and 24 h reaction time, respectively, using the purified enzyme. In comparison, the use of soybean hulls bioconverted only 30 % 2,4-dichlorophenol in 24 h. The toxicity effect of the treated water was evaluated using Lactuca sativa L. var. Buttercrunch as bioindicator. The decreasing in the toxicity after the treatment leads to 100 % germination and 54 % seed root elongation assessments. Overall, we conclude that the studied enzyme and the presented methodology is of interest for soybean hulls lower-value commodity valorisation from a transgenic cultivar.